2021
DOI: 10.1016/j.envint.2021.106380
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of occupational exposure to noise: A systematic review and meta-analysis from the WHO/ILO Joint Estimates of the Work-related Burden of Disease and Injury

Abstract: Highlights WHO and ILO are developing joint estimates of work-related burden of disease and injury. This paper synthesizes evidence on prevalence of occupational noise exposure. 65 studies were included (157,370 participants, 54 countries, six WHO regions). The prevalence of occupational noise exposure in workers was 0.17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 84 publications
1
30
0
1
Order By: Relevance
“…Following scoping reviews, 16 additional pairs of occupational risk factors and health outcomes were selected, which may contribute substantially to the work-related burden of disease. Systematic reviews and meta-analyses were conducted for these pairs to gather evidence for the WHO/ILO Joint Estimates on the prevalence of exposure to occupational risk factors and on the effect of exposure to these risk factors on health outcomes (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The new methods used (28) have been published in an international academic journal (29).…”
Section: Recently Added Pairsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following scoping reviews, 16 additional pairs of occupational risk factors and health outcomes were selected, which may contribute substantially to the work-related burden of disease. Systematic reviews and meta-analyses were conducted for these pairs to gather evidence for the WHO/ILO Joint Estimates on the prevalence of exposure to occupational risk factors and on the effect of exposure to these risk factors on health outcomes (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The new methods used (28) have been published in an international academic journal (29).…”
Section: Recently Added Pairsmentioning
confidence: 99%
“…Additionally, some were identified that had not been included in past estimates but were likely to contribute appreciably to the burden of disease. For these potential new pairs, WHO and ILO conducted a series of systematic reviews and meta-analyses of the WHO/ILO Joint Estimates evidence base, for which protocols were developed, peer-reviewed and pre-published (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). These were carried out with support of experts from government departments in 11 countries (often ministries of health and labor) and over 220 individual experts from 35 countries, covering all six WHO regions.…”
mentioning
confidence: 99%
“…These organizations have produced global, regional and national estimates of exposure to selected occupational risk factors (exposure models) and, consecutively, of the burdens of selected diseases and injuries attributable to these exposures (burden of disease models) (see, for example, Pega et al (2021a) ). They have conducted systematic reviews and meta-analyses of input data for estimating the burden of pairs of occupational risk factors and health outcomes, whose global burdens of disease have never previously been estimated ( Descatha et al, 2018 , Godderis et al, 2018 , Li et al, 2018 , Mandrioli et al, 2018 , Hulshof et al, 2019 , Paulo et al, 2019 , Rugulies et al, 2019 , Teixeira et al, 2019 , Tenkate et al, 2019 , Descatha et al, 2020 , Li et al, 2020 , Pega et al, 2020a , Hulshof et al, 2021a , Hulshof et al, 2021b , Pachito et al, 2021 , Rugulies et al, 2021 , Teixeira et al, 2021b , Teixeira et al, 2021a , World Health Organization, 2021b ). An overview of this series of systematic reviews and its systematic review methodological innovations is provided elsewhere ( Pega et al 2021c ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, road traffic noise may not be the source of noise that raises the most complaints from citizens, but its extent makes it the main source of noise pollution, causing a significant impact on human health. In recent decades, various research studies have shown that exposure to environmental noise poses a significant risk to physical and mental health [2][3][4][5], generating a large burden of disease associated with the exposure dose [6]. The World Health Organization (WHO) [3,4] warns that the negative consequences for the population occur even below the levels recommended for evaluation on strategic noise maps by the Environmental Noise Directive (END) and proposes recommended exposure values for the protection of public health according to the type of source of noise.…”
Section: Introductionmentioning
confidence: 99%